Aggregate-reactivation activity of the molecular chaperone ClpB from Ehrlichia chaffeensis - Zhang, Ting; Kedzierska-Mieszkowska, Sabina; Liu, Huitao; Cheng, Chuanmin; Ganta, Roman R.; Zolkiewski, Michal (My University, 2013)
Rickettsiale diseases, including human monocytic ehrlichiosis caused by Ehrlichia chaffeensis, are the second leading cause of the tick-borne infections in the USA and a growing health concern. Little is known about how E. chaffeensis survives the host-induced stress in vertebrate and tick hosts. A molecular chaperone ClpB from several microorganisms has been reported to reactivate aggregated proteins in cooperation with the co-chaperones DnaK/DnaJ/GrpE (KJE). In this study, we performed the first biochemical characterization of ClpB from E. chaffeensis. The transcript of E. chaffeensis ClpB (EhClpB) is strongly upregulated after infection of cultured macrophages and its level remains high during the Ehrlichia replicative stage. EhClpB forms ATP-dependent oligomers and catalyzes the ATP hydrolysis, similar to E. coli ClpB (EcClpB), but its ATPase activity is insensitive to the EcClpB activators, casein and poly-lysine. EhClpB in the presence of E. coli KJE efficiently reactivates the aggregated glucose-6-phosphate dehydrogenase (G6PDH) and firefly luciferase. Unlike EcClpB, which requires the co-chaperones for aggregate reactivation, EhClpB reactivates G6PDH even in the absence of KJE. Moreover, EhClpB is functionally distinct from EcClpB as evidenced by its failure to rescue a temperature-sensitive phenotype of the clpB-null E. coli. The clpB expression pattern during the E. chaffeensis infection progression correlates with the pathogen’s replicating stage inside host cells and suggests an essential role of the disaggregase activity of ClpB in the pathogen’s response to the host-induced stress. This study sets the stage for assessing the importance of the chaperone activity of ClpB for E. chaffeensis growth within the mammalian and tick hosts.
Citation: Zhang T, Kedzierska-Mieszkowska S, Liu H, Cheng C, Ganta RR, Zolkiewski M (2013) Aggregate-Reactivation Activity of the Molecular Chaperone ClpB from Ehrlichia chaffeensis. PLoS ONE 8(5): e62454. https://doi.org/10.1371/journal.pone.0062454
Keywords: Rickettsiale diseases; Ehrlichia chaffeensis; Tick-borne infections; ClpB